Household politics : conflict in early modern England - Herzog, Don, 1956- (Yale University Press, 2013)
'Household Politics' offers a new look at 'familial patriarchy' in early modern England - an era in which it supposedly thrived. Canonical sources and sermons often urged the subordination of women, but Herzog found that most considered the notion ludicrous. In fact, he found that families experienced a constant negotiation of power, debunking the myth that they were universally patriarchal during this era.